The Overall Efficiency of Mixing in Exchange Flows through Lateral Contractions - Tjipto Prastowo (Jurnal Fisika dan Aplikasinya, 2009)
Laboratory experiments are used to determine the overall (bulk) mixing efficiency in controlled exchange flows past a constriction. The flow generated in the laboratory channel is relevant to natural density-driven exchange flows commonly found in the oceans, where ocean straits control the exchange of waters of different density between adjacent ocean basins, between marginal seas and the open oceans, and within estuaries. The development of Kelvin-Helmholtz billows at the strongly sheared interface generates vertical mixing betweenthe two opposing layers within the constriction. The amount of turbulent mixing is measured and converted to a mixing efficiency, defined as the fraction of the available energy released to kinetic energy of the flow that is converted into an irreversible increase in potential energy of the density field. For simple lateral contractions used in the experiments, the overall mixing efficiency is found to be constant at 11% for large Reynolds numbers, independent of all the external parameters and flow conditions. We conclude from the results that the average efficiency in the oceans is only half of that commonly used in ocean modeling.